2014
DOI: 10.1158/2326-6066.cir-14-0104
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic T Lymphocyte Antigen-4 Blockade Enhances Antitumor Immunity by Stimulating Melanoma-Specific T-cell Motility

Abstract: It is now clear that anti-CTLA-4 (a-CTLA-4) antibodies stimulate tumor immunity either by relieving inhibition of effector T-cell function or by depletion of regulatory T cells (Treg). Several recent reports, however, have suggested that these antibodies may deliver a "go" signal to effector T cells, thus interrupting T-cell receptor signaling and subsequent T-cell activation. We examined the behavior of melanoma-specific CD8 þ pmel-1 T cells in the B16/BL6 mouse model using intravital microscopy. Pmel-1 veloc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 26 publications
(61 reference statements)
1
56
0
Order By: Relevance
“…For other genes like those encoding the chemokine CCL5 (RANTES) and its receptor CCR5, the contribution may be geared more toward T-cell migration, differentiation or the recruitment of other effector cells rather than direct tumor killing. Indeed, increased motility of melanoma-specific T cells was recently attributed to CTLA-4 blockade (26). To support these gene expression results, we analyzed T-bet, Eomes and CCR5 protein expression in transferred T cells from tumor-bearing Alb:Gag mice receiving checkpoint blockade.…”
Section: Resultsmentioning
confidence: 99%
“…For other genes like those encoding the chemokine CCL5 (RANTES) and its receptor CCR5, the contribution may be geared more toward T-cell migration, differentiation or the recruitment of other effector cells rather than direct tumor killing. Indeed, increased motility of melanoma-specific T cells was recently attributed to CTLA-4 blockade (26). To support these gene expression results, we analyzed T-bet, Eomes and CCR5 protein expression in transferred T cells from tumor-bearing Alb:Gag mice receiving checkpoint blockade.…”
Section: Resultsmentioning
confidence: 99%
“…Second, the negative costimulatory molecules, PD1 and CTLA4 have opposing effects on T-cell motility both in vitro and in vivo 41,42 . Finally, recent intravital microscopy data from melanoma models in mice have demonstrated that successful therapeutic anti-CTLA4 treatment correlates with greater T-cell motility 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Anti-CTLA-4 mAbs capable of mediating antibody-dependent cellular cytotoxicity (ADCC) effectively and selectively eliminated intratumoral Tregs, which express higher levels of CTLA-4 compared to circulating Tregs [84-86]. CTLA-4 ligation on effector T cells has also been shown to enhance motility of both CD4 and CD8 T cells [20, 87, 88]. Using CD8 T cells expressing a Pmel-1 transgenic TCR specific for a melanoma antigen Pentcheva-Hoang et al showed that increased motility was associated with tumor rejection, and hypothesized that anti-CTLA-4 may act by reversing motility paralysis of exhausted intratumoral T cells [87].…”
Section: Introductionmentioning
confidence: 99%
“…CTLA-4 ligation on effector T cells has also been shown to enhance motility of both CD4 and CD8 T cells [20, 87, 88]. Using CD8 T cells expressing a Pmel-1 transgenic TCR specific for a melanoma antigen Pentcheva-Hoang et al showed that increased motility was associated with tumor rejection, and hypothesized that anti-CTLA-4 may act by reversing motility paralysis of exhausted intratumoral T cells [87]. …”
Section: Introductionmentioning
confidence: 99%